PENGENDALIAN PERSEDIAAN BAHAN BAKU PADA PROSES WATER TREATMENT MENGGUNAKAN METODE CONTINUOUS REVIEW SYSTEM - Joan Alithea Dayanara (2023)
Drinking Water Management Unit X is a company that uses chemicals in its production process. However, companies often cannot meet consumer demand because they do not yet have standards for chemical inventory control, so it is not uncommon for chemical shortages to occur which also result in various unexpected costs. Then research is needed on chemical inventory control. The purpose of this research is to determine the quantity of chemicals that must be ordered for each order, determine the minimum requirement for chemical supplies and when is the right time to order, and calculate the total inventory cost of chemicals. The method used is linear regression and continuous review system. Based on the research results, the quantity of chemicals that must be ordered for each order with a yearly production capacity of 7,011,097 m3 is 10,988.52 kg of PAC and 5,813.71 kg of chlorine. Minimum inventory of 12.23 kg of PAC and 1.35 kg of chlorine. The right time to place an order is when the remaining PAC stock is 2,189.94 kg, while for chlorine, when the remaining stock is 579.26 kg. The total inventory cost in 2023 for PAC supplies is IDR 1,232,393,321.22 and for chlorine supplies is IDR 408,206,479.97, then the total inventory cost for chemicals in 2023 is IDR 1,640,599,801.19.